Biological effects of new‐generation dialkyl phosphinate flame retardants and their hydrolysates in BALB/C mice. Issue 5 (13th January 2017) - Bao, Jieqing; Liu, Yuchen; Li, Lisha; Chen, Minjie; Liu, Jiyan; Niu, Yumin; Liu, Jingfu; Liang, Yong
Abstract: Aluminum methylcyclohexylphosphinate (AMHP), calcium methylcyclohexylphosphinate (CMHP), aluminum diethylphosphinate (ADEP), and aluminum methylethylphosphinate (AMEP) are organic dialkyl phosphinates (DPs) and emerging phosphorus‐based flame retardants. The broad‐spectrum DPs flame retardants occupy high‐end industrial markets, but their ecologic risk has been reported rarely. By exposing male BALB/c mice to DPs and dialkyl phosphinic acids, we studied the toxic effects of these chemicals, and measured AMHP and methylcyclohexylphosphinic acid (MHPA) in blood and feces. We found that DPs and their main hydrolysates had mild toxicity in BALB/c mice. Exposure to 10 and 50 mg/kg/d of AMEP and ADEP caused mild hepatotoxicity in mice. Toxicity of CMHP was in the liver and kidneys. Toxicity of AMHP and its hydrolysate MHPA was low and affected the liver. These data suggest that AMHP has lower toxicity than the other DPs that we tested. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 1578–1586, 2017.